The body and the sympthom: enjoyment’s treatment in Freud and Lacan - Lima, Christiano Mendes de (Clinical Styles. The Journal on the vicissitudes of childhood, 2013)
This article seeks to outline how body, drives and enjoyment appear articulated in Freud's and Lacan's works. Our aim is to situate the idea that the apparatus said psychic is an assembly for the enjoyment's treatment. We consider that such treatment is touted as ways of tying the real, the symbolic and the imaginary (RSI) by the symthom. We believe that there are borromeans and nonborromeans ways to articulate the RSI, and therefore the constitution of reality. The field of psychosis interests us because, with Lacan, we know that there we have non-borromeans ways of binding the RSI.